2018
DOI: 10.1051/e3sconf/20183003007
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation in Predicting Biochemical Processes and Energy Balance at WWTPs

Abstract: Abstract. Nowadays, the use of mathematical models and computer simulation allow analysis of many different technological solutions as well as testing various scenarios in a short time and at low financial budget in order to simulate the scenario under typical conditions for the real system and help to find the best solution in design or operation process. The aim of the study was to evaluate different concepts of biochemical processes and energy balance modelling using a simulation platform GPS-x and a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…RAS was also discovered to be a major factor in energy consumption as higher RAS resulted in higher energy requirements. This complies with the findings of Drewnowski et al, (2018). In contrast, aluminum sulfate was precipitated to complement the anaerobic tank in phosphorus removal.…”
Section: Model Calibration and Validationsupporting
confidence: 91%
See 2 more Smart Citations
“…RAS was also discovered to be a major factor in energy consumption as higher RAS resulted in higher energy requirements. This complies with the findings of Drewnowski et al, (2018). In contrast, aluminum sulfate was precipitated to complement the anaerobic tank in phosphorus removal.…”
Section: Model Calibration and Validationsupporting
confidence: 91%
“…DO concentrations were found to have a critical role in effluent quality and energy consumption (Drewnowski et al, 2018;Cao et al, 2021;Daskiran et al, 2022). In particular, Cao et al, (2021) found that nitrogen removal was significantly increased by lowering the DO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, there has been a strong demand for the application of mathematical models for the simulation of wastewater treatment processes in full-scale WWTPs [10]. By using computer simulation and advanced programs, it is possible to create a mathematical model of a real WWTP, run a simulation and subsequently interpret results under various conditions without interfering in the actual process performance [11]. Regardless of the process complexity, plant-wide modeling of WWTPs can be used as a base for future applications, optimization studies, or for developing a process for achieving the highest effluent quality levels and energy savings [12].…”
Section: Introductionmentioning
confidence: 99%
“…Models can be used to predict the system response to the appearance of disturbances as well as visualize the effects of configuration changes on the system performance without actually interfering with the system. Nowadays, mathematical modeling of MBR is considered to be an inherent part of the process of designing and managing real objects [10][11][12].…”
Section: Introductionmentioning
confidence: 99%